Konsep Fitrah dalam Perspektif Al-Qur’an dan Pendidikan Islam - Isnaini Septemiarti (LP. Ma'arif Janggan Magetan, 2023)
This study aims to find out the concept of fitrah in the perspective of the Qur'an, what elements are contained in human nature, and how humans develop the nature contained within them through Islamic education. This study uses thematic interpretation, namely by collecting verses of the Koran related to human nature. Through this thematic method we can understand the views and conceptions of the Qur'an regarding fitrah, and its relation to the current development of Islamic education. Fitrah in the view of the Qur'an has several dimensions. The natural dimensions referred to in this case are the aspects contained in human nature which have many variations. This diversity is caused by different points of view. There are three human dimensions which are the essence of its creation or its totality, namely the physical, psychological and psychophysical dimensions or in Islam known as bodily fitrah (al-jism), spiritual fitrah (al-ruh) and nafsiyyah fitrah (al-nafs). Human nature can develop properly through the educational process.